2013
DOI: 10.1192/pb.bp.111.037705
|View full text |Cite
|
Sign up to set email alerts
|

Community treatment orders: current practice and a framework to aid clinicians

Abstract: Aims and methodCommunity treatment orders (CTOs) have been used more than anticipated. We report data from the North Wales audit about their current use and explain how a SMART framework can be used to potentially improve their effectiveness.ResultsFindings from this audit confirm those from other studies, with the reasons for use of CTOs extending beyond that of medication adherence to risk management. The combined recall and voluntary admission rate was 40%, which raises questions about the effectiveness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…These findings are in line with local studies: A 12 month follow-up of 65 CTOs in North England reported a 40 % recall rate over 12 months [21] and an audit of 50 CTOs in North Wales reported a 34 % recall rate [23]. These studies reported very different rates of revocation, however, 96 % [21] and 34 % [23] respectively.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings are in line with local studies: A 12 month follow-up of 65 CTOs in North England reported a 40 % recall rate over 12 months [21] and an audit of 50 CTOs in North Wales reported a 34 % recall rate [23]. These studies reported very different rates of revocation, however, 96 % [21] and 34 % [23] respectively.…”
Section: Discussionsupporting
confidence: 85%
“…These studies reported very different rates of revocation, however, 96 % [21] and 34 % [23] respectively. Two 6-month follow-ups (of 104 and 67 patients respectively) saw lower recall rates of 19 % [19] and 13 % [24], possibly due to the short time frame.…”
Section: Discussionmentioning
confidence: 99%
“…Socio-demographic and clinical characteristics of the sample are presented in Table 1. Of the 114 patients, 76 (67%) were male, 56 (49%) were White British, 37 (33%) were Black, 15 (13%) were The characteristics of this sample closely match those of other CTO studies in the UK and internationally [1,29,30].…”
Section: Baseline Characteristicssupporting
confidence: 65%
“…Most are single, live in rented accommodation alone or, less often, with their family, and almost none are in regular employment (Dawson 2005; Churchill 2007). This is also the group of patients on CTOs in the UK (Evans 2010; Care Quality Commission 2011; Dye 2012; Lepping 2013; McKie 2014; Rawala 2014; Smith 2014). Less than 5% of CTO patients in England and Wales are discharged onto a CTO from court-ordered hospital admission (Health and Social Care Information Centre 2015).…”
Section: The Spread and Use Of Cto Legislationmentioning
confidence: 99%
“…the order stops and compulsory hospital treatment is imposed). The most frequently stipulated conditions written into virtually all CTOs are to take medication as prescribed and to remain in contact with the mental health team (Care Quality Commission 2011; Lepping 2013; Smith 2014; Rugkåsa 2017). Around a third of CTOs require the patient to live at a specified address (Rugkåsa 2017).…”
Section: The Spread and Use Of Cto Legislationmentioning
confidence: 99%